Market Segmentation Through Information - Elliott, Matthew; Galeotti, Andrea; Koh, Andrew; Li, Wenhao (Review of Economic Studies, 2026)
Abstract We explore the power that precise information about consumers’ preferences grants an intermediary in shaping competition. We think of an intermediary as an information designer who chooses what information to reveal to firms, which then compete à la Bertrand in a differentiated product market. We analyse the information designs that maximize consumer and producer surplus and uncover systematic differences in how information can be used to intensify or soften competition. Our analysis demonstrates the power that users’ data can endow intermediaries with and speaks directly to current regulatory debates regarding digital marketplaces.